Morphological and biochemical characterization of two fish pathogenic bacteria: Aeromonas salmonicida and Yersinia ruckeri for rapid diagnosis of fish disease - Akter, Tasmina (Asian Journal of Medical and Biological Research, 2017)
Aeromonas salmonicida and Yersinia ruckeri are two common pathogenic fish bacteria responsible for furunculosis and Enteric Red Mouth disease (ERM), respectively. For the characterization of these two pathogens, a series of morphological (pigmentation, hemolyse, motility and body shape), biochemical tests (Gram staining, catalase, oxidase and API 20E strips) and a soft ionization technique (MALDI-TOF/MS) were performed in the laboratory. Pigmentation, motility, hemolysis and body shape was used as a preliminary identification of the bacteria. Both of the species were identified with the entire biochemical test without any doubt except API20E strips test. Although the API profile of A. salmonicida (0006104) was identified with high confidence (99.6%), but Y. ruckeri was misidentified as Vibrio mimicus. There are strong supports against Vibrio mimicus as it is a human pathogen, grow at a temperature more than 20oC, motile and oxidase positive bacteria. The Y. ruckeri is a non-motile fish bacteria and oxidase negative which are consistent with the study results. Agglutination test with Bionor Mono kit was also identified the bacteria as Y. ruckeri. For rapid diagnosis of infectious disease, accurate identification of pathogen is very important for commercial aquaculture. Asian J. Med. Biol. Res. March 2017, 3(1): 44-51